The Role of Elderly Cadres in the Prevention and Control of Hypertension - Marsito Marsito; Rina Saraswati; Ernawati Ernawati (Universitas Muhammadiyah Semarang, 2025)
Hypertension is a health problem in Indonesia, with increasing prevalence, while efforts to maintain it are still lacking. National health research data shows a prevalence of 34.11%, and the current prevalence in Indonesia has reached 45.9%, which is considered high. This study aims to examine the role of health cadres in intervening in elderly hypertension. We compare the blood pressure of elderly who received the intervention and the control group. The research method used a paired t-test in the intervention group, and the control group was conducted by cadres. We compared the results of elderly blood pressure measured by health cadres with the intervention group without education as a control. The results in the intervention group for elderly hypertension were p = 0.0002, while in the control group, p = 0.040. This means that both groups experienced a decrease in blood pressure in elderly hypertension in the intervention and control groups. However, a significant decrease occurred in the intervention group. This means that cadres providing education to elderly hypertension quickly reduce blood pressure compared to those who did not receive education. Therefore, the role of cadres is very important in reducing the prevalence of hypertension control.